2000
DOI: 10.1103/physrevb.62.14164
|View full text |Cite
|
Sign up to set email alerts
|

Dzyaloshinskii-Moriya interaction inNaV2O5:A microscopic study

Abstract: We present a unified account of magnetic exchange and Raman scattering in the quasi-one-dimensional transitionmetal oxide NaV2O5. Based on a cluster-model approach explicit expressions for the exchange integral and the Ramanoperator are given. It is demonstrated that a combination of the electronic-structure and the Dzyaloshinskii-Moriya interaction, allowed by symmetry in this material, are responsible for the finite Raman cross-section giving rise to both, oneand two-magnon scattering amplitudes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 35 publications
(55 reference statements)
2
10
0
Order By: Relevance
“…Subsequent structure redetermination for the HT phase of α ′ -NaV 2 O 5 [2][3][4][5] does not, however, allow to ascribe E a polarized spectral continuum to a pure twospinon absorption. Symmetry considerations show that for both HT-and LT-structure of α ′ -NaV 2 O 5 the two-spinon (two-magnon) absorption is allowed only in E c polarization [33,34]. Probably, a weak FIR absorption background observed in this polarization results just from the two-spinon absorption.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent structure redetermination for the HT phase of α ′ -NaV 2 O 5 [2][3][4][5] does not, however, allow to ascribe E a polarized spectral continuum to a pure twospinon absorption. Symmetry considerations show that for both HT-and LT-structure of α ′ -NaV 2 O 5 the two-spinon (two-magnon) absorption is allowed only in E c polarization [33,34]. Probably, a weak FIR absorption background observed in this polarization results just from the two-spinon absorption.…”
Section: Resultsmentioning
confidence: 99%
“…The transitions between the singlet ground state and the excited triplet state are forbidden (∆S = 1). The Dzyaloshinsky-Moria (DM) interaction with DM vector along the c-axis breaks the selection rule for ESR (and FIR) E c transitions in α ′ -NaV 2 O 5 [37,34]. Recently, it has been shown theoretically [34] that for α ′ -NaV 2 O 5 the DM interaction results in finite Raman cross-section for both one-and two-magnon scattering processes.…”
Section: B Magnetic Bound States?mentioning
confidence: 99%
See 1 more Smart Citation
“…͑52͒ should be taken into consideration. 40 However, the above result does not change, taking Eqs. ͑53͒ and ͑54͒ into account.…”
Section: ͑58͒mentioning
confidence: 88%
“…It is very weak and detectable under the resonant condition, and splits into two peaks when magnetic fields are applied parallel to the b and c axes, but it neither shifts nor splits when a magnetic field is parallel to the a axis. Valentí et al 40 theoretically studied Raman scattering in quasi-one-dimensional antiferromagnetic spin chains considering the Dzyaloshinskii-Moriya ͑DM͒ interaction. They concluded that a single magnon excitation probed by Raman scattering should show no splitting in external magnetic field parallel to the DM vector D and it should split into two branches for a field perpendicular to the DM vector.…”
Section: ͑44͒mentioning
confidence: 99%